A T-shape diphosphinoborane palladium(0) complex - Steinhoff, Patrick; Tauchert, Michael E. (Beilstein Journal of Organic Chemistry, 2016)
The reaction of CpPd(η3-C3H5) with the new diphosphinoborane ligand derivative (o-PCy2-C6H4)2BPh CyDPBPh affords the T-shape complex (CyDPBPh)Pd(0) 9, which was characterized by X-ray analysis.
Keywords: ambiphilic ligand; coordination chemistry; diphosphinoborane; organometallics; palladium